Fabrication of flexible blade models from a silicone‐based polymer to test the effect of surface corrugations on drag and blade motion. (16th July 2015) - Fryer, M.; Terwagne, D.; Reis, P. M.; Nepf, H.
Abstract: Macrocystis blades develop longitudinal corrugations in regions with strong current and wave action. This study examined the effect of corrugations on blade motion and blade drag by constructing flexible blades with different corrugation amplitude and a control blade with no corrugation. The models were designed to be dynamically and geometrically similar to natural blades. Acrylic molds were etched using a laser cutter and filled with a silicone‐based polymer to create flexible model blades with sinusoidal corrugations. The corrugated and flat model blades were tested in a water channel using drag force measurements and video analysis. The corrugated blades experienced a drag per surface area reduction of up to 60% compared to the flat blade. Additionally, the corrugated models exhibited smaller motion, as quantified by the maximum vertical displacement. The reduction in drag may explain why corrugations are observed in exposed regions of high current and wave action, where a reduction in drag provides important protection against breakage.